2019
DOI: 10.1186/s12877-019-1331-8
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalized elder abuse in Iran: a qualitative study

Abstract: BackgroundElder abuse is a serious violation of human rights and a worldwide issue. Upon hospital admission, elderly patients become vulnerable and susceptible to abuse. Understanding the issues perceived as abuse by the elderly patients and their family members allows us to identify, manage, and prevent elder abuse; especially in hospital settings. The present study aimed to identify and describe the abuse of hospitalized elders from the perspective of patients and their family members.MethodsThe present expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 38 publications
1
32
0
9
Order By: Relevance
“…The mistreatment older adults experience from healthcare professionals during the COVID‐19 pandemic confirm the known research findings indicating that older people are vulnerable to abuse when they visit the hospital to seek medical treatment (Naderi et al., 2019; Rosen et al., 2018). This event is unfortunate, and it is a severe infringement of older adults' inherent right to be treated with respect and courtesy.…”
Section: Discussionsupporting
confidence: 74%
“…The mistreatment older adults experience from healthcare professionals during the COVID‐19 pandemic confirm the known research findings indicating that older people are vulnerable to abuse when they visit the hospital to seek medical treatment (Naderi et al., 2019; Rosen et al., 2018). This event is unfortunate, and it is a severe infringement of older adults' inherent right to be treated with respect and courtesy.…”
Section: Discussionsupporting
confidence: 74%
“… 71 , 72 Mistreatment includes psychological abuse by restricting decision-making, 73 ignoring older people’s preferences and coercing them into following instructions from professionals. 74 The psychological abuse of older people was reflected in our results. There is limited research evidence to support the development of best practice, 75 and further studies are needed to identify how to prevent violating older people’s autonomy.…”
Section: Discussionmentioning
confidence: 51%
“… 34 In a qualitative study among older adult patients, Naderi and colleagues reported similar findings. 35 Another qualitative study reported that healthcare specialists tend to exclude older adult patients from discussions about their medical condition, instead they decide on their own or involve a younger family member. 20 This is despite the fact that the involvement of older adult patients in the decision-making process would positively affect their satisfaction level and lead to better treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%